Quality Test of Cooking Oil Used by Fried Chicken Sellers in the Ciamis Market Based on Peroxide Value - Achlina , Dean Nur; Nurazizah, Asyifa (Ad-Dawaa : Journal of Pharmacy, 2024)
Oil is a source of energy for humans that produces energy of 9 kcal / gram. One way to show oil quality can be seen based on peroxide numbers. According to the 2013 Indonesian National Standard regarding cooking oil quality requirements, the peroxide number limit is 10 meq O2/kg. The purpose of this study was to determine the quality of cooking oil in fried chicken traders in the Ciamis market. The factor that influences changes in peroxide numbers in oil is the duration of heating. The method used to find out the peroxide number is iodometric titration. The results obtained are the volume of the titrant and the weight of the sample used. Analysis of the data generated using the peroxide number formula. Based on research, the quality test of cooking oil shows that cooking oil in 5 fried chicken traders in Ciamis Market exceeds the maximum limit of peroxide numbers, namely with a sample average of A 31.89 mek O2 / kg; sample B 48.88 mek O2 / kg; sample C 34.67 mek O2 / kg; sample D 46.11 mek O2 / kg; and sample E49.23 mek O2 / kg. So the conclusion of this study, the cooking oil used by 5 traders of fried chicken in Ciamis Market does not meet SNI standards so that it can have a negative impact on health.